Arts Communication Model: The Development of Performing Arts through Empowering Cultural Art-Based Tourism - Jaeni, Jaeni (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2023)
Indonesia has many traditional’s arts. However, not all Indonesian people treat them to protect sacred objects since art is considered as a finished cultural product. Considering that the performing arts have not been well communicated for providing and empowering the community’s benefits except for home entertainment and stage performances, this research aims to create a model of performing arts communication through empowering cultural art-based tourism. The research method used is a qualitative approach and creative artwork using the RD method by analyzing various performing arts in West Java, by collaborating on art’s packaged in the form of tourist performance, field tests are carried out through performances in tourist areas, performances through art’s festivals. This research resulted in a workflow for developing cultural art to create art products and cultural art-based tourism spaces to arrive at a model of performing art’s communication. An important contribution from the perspective of performing arts communication is the understanding of value relations between actors and their public. Social, cultural, economic, political, educational, environmental, and tourism’s values become meaningful references in creating art and tourism spaces for the community’s sustainable development.